Application of the Authority Control process in the Koha Software (LIS TODAY, 2023)
In modern library management system users take help from the Online Public Access  Catalogue (OPAC) to find their required documents available in the library. This study focuses on the  Authority Control process in computerized cataloguing management of library documents. Authority  Control process is a key concept of OPAC where users find out their topics in easy way. The present  paper structured by practical observations of the Authority Control process in Koha software. Several  authority control methods were applied during this study and all have been mentioned through  different figures available in this paper. The practical approaches are remembered for the piece of  the procedure utilized for the assessment of this paper. Thus, the specialized abilities and different  angles are methodologies of this exploration paper. If the authority control system is applied while  entering the bibliographic details of the documents stored in the library, the task of searching the  information by the reader also becomes simplified besides making the database of the library strong.
Keywords: Authority Control; Koha; Library Cataloguing; MARC21; OPAC